Evaluation of the Implementation of Occupational Safety and Health in the Construction of a Four-Storey Building (Case Study: Construction of the Ishk Tolaram Eye Clinic in Batu City) - Fifi Damayanti; Handika Setya Wijaya; Suhudi (Jurnal Penelitian Pendidikan IPA, 2025)
Construction remains a highly hazardous industry, and strengthening Occupational Safety and Health (OSH) is urgent to reduce injuries and occupational illnesses while sustaining productivity. However, in four-storey construction, OSH is often treated as compliance, and evidence is limited on its measurable contribution to workforce effectiveness and on which OSH factors should be prioritized. This study evaluated OSH implementation in the Ishk Tolaram Eye Clinic (four-storey) project in Batu City, Indonesia, using observations and questionnaires from supervisors and artisans/forepersons, analyzed with SEM-PLS. The structural model shows a strong, positive, and significant effect of OSH implementation on workforce effectiveness (path coefficient = 0.76; t = 13.46; p = 0.00). OSH implementation explains 58.0% of the variance in workforce effectiveness (R² = 0.58); occupational health is the most dominant OSH dimension (loading = 0.72), and adequate sanitation conditions (X2.4) are the key leverage point (loading = 0.80). This research contributes a multidimensional, evidence-based evaluation framework that converts OSH from a checklist into prioritized drivers linked to workforce outcomes. In practice, contractors should prioritize occupational health controls, especially sanitation, alongside training and PPE discipline, to improve safety performance and reliable productivity across comparable four-storey projects in Indonesia.